(untitled) (Journal of Asian Development Studies, 2015)
This study examines the socio-economic role of private investment in ownership of dwellings using time series data for the period of 1981-2010. The investment accelerator model is used in the study and regressed through OLS method. The variables included in the study are Private Investment in Ownership of Dwellings (Ipd) and the independent variables are Value-Added in Ownership of Dwellings (Vod), Population Growth Rate (Popg), Remittances (Rm), Weighted Rate of Interest (rw), Exchange Rate (ER) and dummy variable (Dps) for the political stability and favorable effect of revival of democracy and privatization. All the variables are significant with desired sign showing the positive effect of private investment on ownership of dwellings. The study also suggested some policy recommendation for the government to bring more improving in the investment and output.